Implementation and evaluation of biosecurity programs in pig production. A Review - Gamero Aguilar, Carlos Eduardo [UNESP]; Baraldi, Thais Gasparini; Ramos dos Santos, Anne Caroline [UNESP]; Nascimento, Karla Alvarenga [UNESP]; Franco Oliveira, Maria Emilia [UNESP]; Oliveira, Luis Guilherme de [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2015)
Intensive and large-scale system pork production prioritizes practices which reduce spread of infeccious diseases, improving health pig herd, reducing outgoing and deaths. Therefore, biosecurity programs have been required to control or eradication of pathogens on farms. The aim of the paper is identify the agents spread critical points on pig production, indicating control measures through biosecurity technique.
Keywords: health; infectious diseases; prevention; swine